Composite nanoparticle-based vesicles achieve enhanced delivery effects of the natural plant extract of the root, stem, and fruit - Zhuang, Xiaodong; Ma, Ting; Liu, Risheng; Fang, Xingyue; Huang, Liangjiu (Frontiers in Chemistry, 2025)
The extract of medicinal plants is increasingly popular around the whole world due to its attractive therapeutic effects. However, the bioavailability of the extract of bioactive compounds was barely satisfactory due to its easily deactivated and untargeted properties. The use of nanotechnology to develop novel carrier delivery techniques for bioactive extracts has been proven to have significant potential and provides an amazing improvement in the therapeutic effect. Calcium carbonate nanoparticles (CaCO3 NPs), as representative biodegradable materials, are well recognized as environmentally responsive delivery vehicles for disease treatment. In this study, extracts of the root of ginseng, the fruit of Alpinia oxyphylla Miq., and the stem of Millettia speciosa Champ. were developed as a CaCO3 nanoparticle loading drug. All of the three composite nanoparticles exhibited spherical shapes with a narrow size distribution. Notably, the ginseng extract-loaded CaCO3 NPs hold a relatively higher entrapment efficiency of up to 55.2% ± 6.7% and excellent release performance under acidic conditions (pH = 5.5). Moreover, intravenous injection of ginseng CaCO3 NPs resulted in significantly enhanced therapeutic effects in the treatment of glioma. The results demonstrate that CaCO3-based composite nanoparticles are ideal for the delivery of plant extracts, and the systems are expected to be effective against various types of diseases in the future.